Managing paraffin wax deposition in oilwell - Abdul Kadir, Abdul Aziz; Ismail, Issham; Sengodan, Papathy (Faculty of Engineering, UPM, 1999)
The presence of paraffin wax in crude oil has cause flow and mechanical problems while the oil is flowing from the wellbore via surface production tubing, facilities and trunkline to the crude oil terminal. Accurate knowledge of the potential for, and extent of, wax deposition can be critical in the successful design and operation of hydrocarbon production systems. Temperature is observed to be the main factor that controls the saturation of paraffin wax in oil. The decrease of temperature will result in the appearance of wax crystals. A simplified mathematical model was developed to predict the change of saturation of crude oil at subsequent temperature drops along the flow conduit. Paraffin wax crystallization occurs when the temperature of the oil drops below the wax appearance temperature. In this paper the authors present the causes and effects of such deposition and introduce predictive model to assist the prevention and mitigation measures through a case study.